Model Manajemen Pendidikan Inklusif dan Berkelanjutan di Tingkat Sekolah Dasar di Jakarta: Studi Konseptual - Sutikno, Sutikno; Nurhattati, Nurhattati; Madhakomala, Madhakomala (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
Elementary education in Jakarta faces challenges stemming from diverse student characteristics, socioeconomic disparities, and demands for sustainable school practices. This study aims to formulate a conceptual model for inclusive and sustainable education management at the elementary school level. The analysis focuses on five key issues: responsive curriculum, adaptive resource management, school community participation, inclusive school culture, and environmentally friendly culture. The approach is a conceptual study using descriptive qualitative methods, based on a synthesis of international literature and national policies related to inclusive and sustainable education. Thematic analysis identifies critical issues and integrates inclusive and sustainable principles into school management. Findings indicate that a differentiated curriculum, needs-based resource allocation, community collaboration, internalization of inclusive values, and environmentally conscious behavior are essential foundations. This study proposes a conceptual model as a strategic reference for schools and policymakers.